Implementing the Contingent Valuation Method for supporting decision making in the waste management sector. (July 2016) - Gaglias, A.; Mirasgedis, S.; Tourkolias, C.; Georgopoulou, E.
Highlights: We apply Contingent Valuation for estimating externalities of landfills for residues. Adoption of compensatory benefits facilitates the social acceptance of landfills. Environmental externalities attributed to landfills for residues are relatively low. Assessed externalities provide a basis for the magnitude of compensatory benefits. Abstract: This study presents an application of the Contingent Valuation Method (CVM) for valuing the environmental impacts associated with the operation of landfills for residues following waste treatment and depicts how the results of the analysis can be used for decision making in the field of waste management. The survey was conducted in Ikaria, Greece, a medium-sized island in the northern Aegean Sea, with a view to estimate the amount of compensatory benefits that are socially acceptable to be attributed to the hosting community of a new landfill for residues. The results showed that the mean willingness to pay per household to create a fund for financing social and environmental programs in the community that will host the landfill in question was estimated at €6.5–6.7 per 2-month and household taking into account all households of the sample. This estimate is at the same order of magnitude but at the lower band compared to the results of other relevant studies showing that the public in Ikaria is aware for the relatively limited environmental burdens associated with the operation of landfills for residues following an integrated waste management treatment.